Optimization for Detection of On-Site Phosphate Contamination Qualitatively - Hashim, Saiyidah Nafisah; Rodzali, Nur Nadirah; Muhammad, Noor Amira; Abdullah, Siti Nur Azmu’i; Hasmi, Nur Atirah; Kamarudin, Amir Arif; Nor Azlan, Siti Nor Anissa; Saharudin, Nurul Syahniza; Nor Rahim, Nur Fatin Afiqah (Journal of Science and Mathematics Letters, 2019)
Water pollution is a serious case when the amount of phosphate exceeds the safe level. This phenomenon will lead to eutrophication so it affects the underwater organism. Therefore, water samples at site sites need to be tested directly so that contamination can be detected immediately. The objective of this study is to design a test kit to detect phosphate content in water by minimizing the use of reagents and water samples. The quantities of reagents tested were ammonium molybdate (0.5 and 1 mL) and stannous chloride (1 and 2 drops) at different phosphate concentrations. The quantities of reagents that have been identified were then tested on the number of different water samples (25, 20, 15, 10 and 5 mL) and color changes were documented. It has been identified that the volume of reagents for identification of phosphate contamination, respectively is 0.5 ml and 1 drop of reagents for molybdate and stannous chloride. Whereas, the minimum amount of water required for this test is 15 ml. The phosphate test kit is then specially designed and the accuracy of the reading kit has been identified by conducting a qualitative phosphate contamination test in the pool or river area directly on three different water samples. Quantitative analysis is also done by reading pollution via UV-Vis spectrophotometer. There was little difference in the amount of phosphate content through both analyses.